Discussion - Of Mr. Keyes's Paper on Genesis of the Lake Valley. New Mexico, Silver- Deposits (see p. 139) (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1909)
Bernard MacDonald, Guanajuato, Mexico (communication to the Secretary*):—Mr. Iceyes's paper is very interesting to me because of my personal experience with the development of the ore-deposits of Lake Valley.